26: Prevalence, Practice Patterns and Hematological Outcomes of Young Canadian Children Identified with Non-Anemic Iron Deficiency (NAID): Implications of Screening in Primary Care Settings. Issue 6 (1st June 2014) - Abdullah, K; Maguire, JL; Birken, CS; Thorpe, KE; Hanley, AJ; Fehlings, D; Parkin, PC
Abstract: BACKGROUND: There is emerging evidence that non-anemic iron deficiency (NAID) in early childhood may be association with poor health and developmental outcomes. Some guidelines recommend screening for iron deficiency anemia; however, the role of screening for NAID is unknown. OBJECTIVES: Our overall objective was to evaluate outcomes following screening for NAID. Our specific objectives were: to determine the prevalence and risk factors associated with NAID in pre-school children; describe the practice patterns associated with the management of NAID in primary care settings; and describe the hematological outcomes of NAID with or without treatment. DESIGN/METHODS: A cohort study of healthy children, aged one to five years, seen for primary health care between July 2008 and June 2012 was conducted through the TARGet Kids! practice based research network. Descriptive statistics were used to describe the prevalence, risk factors, practice patterns and the hematological outcomes of children identified with NAID (defined as serum ferritin level ≤12 μg/L and a hemoglobin level ≥110 g/L). The association between NAID and potential risk factors were examined using a multivariate logistic regression analysis. RESULTS: Of 2276 children undergoing screening, 155 had NAID, for a prevalence of 7% (95% CI 5.95 to 8.05%). Risk factors significantly associated with NAID included younger age and those with higher zBMI. An assessment of practice patterns revealed that for 57 of 155 children (37%) an intervention for NAID was recommended (diet, oral iron or both); and for 14 of 155 children (9%) a follow-up blood test was completed to reevaluate their iron status. An assessment of the hematological outcomes of NAID with treatment (n=57) revealed that of the 14 children with a follow-up blood test, 11 children resolved their NAID and in three cases NAID did not resolve. An assessment of the hematological outcomes of NAID without treatment (n=98), revealed that of the 26 children with a follow-up blood test, NAID resolved in 17, did not resolve in eight, and in one child progressed to iron deficiency anemia. CONCLUSIONS: This study shows that NAID is a prevalent condition in young Canadian children; that there is substantial practice variation in management of NAID following screening. Further research is necessary to understand the benefits of screening for NAID and evidence-based practice guidelines are needed to manage NAID in early childhood.